Prevalence of multiple long-term chronic conditions and associated disabilities among community-dwelling adults in Riyadh - Alenazi, Aqeel M.; Alhwoaimel, Norah A.; Alqahtani, Bader A.; Alshehri, Mohammed M.; Alhowimel, Ahmed S.; Khunti, Kamlesh (Frontiers in Public Health, 2024)
Background/Objectives Saudi Arabia is experiencing a rapid rise in chronic diseases and disability. However, there is a dearth of research on these topics in the Arab world. This study aimed to examine the prevalence of multiple long-term chronic conditions (MLTC) and disability and their relationship. Method The survey was conducted in Riyadh in Saudi Arabia in 2023. Convenient sampling was used to select 324 participants aged 50 and older, with data on disability status. The survey collected information on age, sex, body mass index (BMI), multiple long-term chronic conditions - MLTC or multi-morbidity, and activities of daily living. Disability was measured using Arabic versions of basic ADL and Barthel Index. Results: The prevalence MLTC among participants was 49.4%. The prevalence of disability using ADL and Barthel Index were 33.6% and 49.7%, respectively, and these rates increased 42.5% and 58.1%, among participants with MLTC (n=160). MLTC was associated with increased risk of disability using ADL (Odds Ratio (OR) 1.99, p=0.037) and Barthel index (OR 2.27, p=0.007). Conclusion: Approximately half of the participants with disability data had MLTC, and about third to half had disability. MLTC was significantly associated with any kind of disability in community Saudi adults. Hence, strategies to reduce chronic diseases may result in reduction in disability, and vice versa.